2003
DOI: 10.1021/jm020990u
|View full text |Cite
|
Sign up to set email alerts
|

Orally Active Analogues of the Dopaminergic Prodrug 6-(N,N-Di-n-propylamino)-3,4,5,6,7,8-hexahydro-2H-naphthalen-1-one:  Synthesis and Pharmacological Activity

Abstract: A series of analogues of 6-(N,N-di-n-propylamino)-3,4,5,6,7,8-hexahydro-2H-naphthalen-1-one (6), an enone prodrug of the mixed DA D(1)/D(2) agonist 5,6-diOH-DPAT (2), was synthesized. The pharmacological profiles of these new enones and their in vivo pharmacological activities were investigated in the Ungerstedt rat rotation model for Parkinson's disease. At 0.1 mg kg(-1) po, the N-methyl-N-n-propyl (12) and the N-ethyl-N-propyl (13) analogues induced pronounced and long lasting pharmacological effects. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[39] It has also been shown that the removal of one hydroxy group from (R)-NPA, as in (R)-11-hydroxy-N-(n-propyl)norapomorphine, only has a moderate effect on the pharmacological profile in terms of agonism and affinity for the D 2 receptor. [42] This is also true for the analogues (R)-5,6-dihydroxy-DPAT and the monohydroxy-substituted (S)-5-OH-DPAT (8 a), [43] which confirms that only one hydrogen bond acceptor/donor group is important for potent D 2 agonism. The semi-flexible aminothiazole derivative talipexole (2) is a full agonist that shows high selectivity for D 2high .…”
Section: Dataset Of Dopamine D 2 Ligandsmentioning
confidence: 70%
See 1 more Smart Citation
“…[39] It has also been shown that the removal of one hydroxy group from (R)-NPA, as in (R)-11-hydroxy-N-(n-propyl)norapomorphine, only has a moderate effect on the pharmacological profile in terms of agonism and affinity for the D 2 receptor. [42] This is also true for the analogues (R)-5,6-dihydroxy-DPAT and the monohydroxy-substituted (S)-5-OH-DPAT (8 a), [43] which confirms that only one hydrogen bond acceptor/donor group is important for potent D 2 agonism. The semi-flexible aminothiazole derivative talipexole (2) is a full agonist that shows high selectivity for D 2high .…”
Section: Dataset Of Dopamine D 2 Ligandsmentioning
confidence: 70%
“…Malmberg et al [38] and Payne et al [19] studied a set of enantiomerically pure mono-and dihydroxylated aminotetralines for both binding and functional properties. They showed that (S)-5-OH-DPAT (8 a) is a full D 2 agonist, although not fully selective, [43] whereas its enantiomer 8 b is a partial agonist that shows low affinity for D 2high . [38] A compound with more sterically demanding N substituents is rotigotine, which shows D 2 receptor selectivity and a high K i D 2low /D 2high ratio.…”
Section: Dataset Of Dopamine D 2 Ligandsmentioning
confidence: 99%
“…proposed the synthesis and pharmacological evaluation of the orally active enone prodrug S-(-)-6-(N,N-di-n-propylamino)-3,4,5,6,7,8-hexahydro-2H-naphthalen-1-one [(-)- 114 (S-PD148903)]. 1-4 Bioactivation of enones by metabolic conversion to their corresponding catecholamines, as was demonstrated for (-)- 114 , is thought to be the general bioactivation mechanism ( Figure 19 ) [ 85 , 86 , 87 ]. Compound S-PD148903 represents a new type of prodrug which in the rat is bioactivated to the catecholamine S-5,6-diOH-DPAT ( 115 ), known to display mixed DA D1/D2 receptor agonist properties just like apomorphine.…”
Section: Dopamine Receptor Agonist Prodrugsmentioning
confidence: 99%
“…2 Furthermore, several analogues of 1 with different N-alkyl substituents induce similar or more potent dopaminergic effects. 3 Evidently, the aminotetralin-derived analogues of 1 contain a "template" for bioactivation.…”
Section: Introductionmentioning
confidence: 99%